Compressive stress-strain behavior of HSFRC reinforced with basalt fibers - Ayub, T. (American Society of Civil Engineers (ASCE), 2016)
Fiber-reinforced concrete (FRC) is a well-recognized construction material because of its vast application in civil engineering structures. The use of steel fibers in FRC is well established in terms of reliable modeling of its mechanical characteristics; however, new fiber reinforcements also need attention. This paper analyzes the compressive stress-strain behavior of three mix types of high-strength fiber-reinforced concrete (HSFRC) having compressive strengths of 70-85 MPa and containing 1-3 volume fractions of basalt fibers. In the first mix of HSFRC, 100 cement content was utilized whereas 10 cement content was replaced by silica fume and metakaolin as replacement materials in the remaining two mixes. Based on the experimental data, an analytical model to predict the complete stress-strain behavior of HSFRC is proposed that shows good agreement with experimental results. Â© 2015 American Society of Civil Engineers.